Manual de buenas prácticas de manufactura para la empresa “Aluminios Hércules”. - Saez Condor, Angel Geovanny (2021)
This project analyzes all the production processes used to manufacture kitchen utensils, with the use of aluminum as a raw material, and the application of the INEN 2361 standard to improve productivity. It began with the characterization of the company's production processes, flowcharts and processes were developed to know the initial state of the company. To define the existing problems in the company, an Ishikawa diagram was made, with which the main shortcomings incurred in the manufacture of kitchen utensils used for food preparation were identified. In the initial phase, a survey was carried out among the workers, to verify their knowledge about the application of the INEN 2361 standard, and the requirements that it demands. For compliance with the standard, a check list of the requirements it contains was carried out, as results it was obtained, which does not apply to all the products that are manufactured in the company, there is a lack of training on the standard for the manufacture of pressure cookers. aluminum, low supply and inadequate use of EPPS and improper handling of raw materials. The application of the matrix of times and movements helped to define the unproductive times and the bad location of the work areas. After having compiled all this information, it was taken as a reference to define the aspects and requirements that are used to improve the production process of the manufacture of aluminum pots, and the application and use of the proposed GMP manual is recommended.